Cognitive effects of endocrine therapy for breast cancer: keep calm and carry on? - Zwart, Wilbert; Terra, Huub; Linn, Sabine C.; Schagen, Sanne B. (Nature reviews. Clinical oncology, 2015)
Key Points Preclinical and clinical data indicate that endocrine treatment for breast cancer might have an adverse effect on cognition Many studies exploring the influence of endocrine therapy on cognition are underpowered and have flawed designs, precluding any definite conclusions on the existence and clinical impact of such effects Studies with a pretreatment neuropsychological assessment are essential to determine the potential cognitive effects of endocrine treatment and to identify patients who might be at risk of treatment-associated cognitive decline Current guidelines permit the choice between different endocrine regimens in the treatment of breast cancer; thus, potential treatment-selective cognitive effects might influence treatment decision-making on an individualized basis Many breast cancer survivors experience long-term adverse effects of adjuvant systemic therapy, including cognitive decline. The decline of cognitive functions can have a detrimental impact on quality of life and might interfere with independent living. This Review discusses the tissue-selective side effects of endocrine therapies and specifically their impact on cognitive function. The critical issues that need to be addressed to best assess the cognitive effects of endocrine treatment in patients with breast cancer are highlighted. The number of breast cancer survivors is gradually increasing and a subset of these patients experience long-term adverse effects of adjuvant systemic therapy, including cognitive decline. Surprisingly, relatively little is known about the long-term adverse effects of endocrine treatment on cognition. As 75% of all patients with breast cancer are eligible to receive hormonal treatment, understanding the potential neurocognitive adverse effects of such therapy is of utmost importance. Concerns about adverse cognitive effects of adjuvant endocrine therapy are timely, as recently updated guidelines recommend increasing the length of such therapy from 5 years to 10 years for a subset of patients. The decline of cognitive functions can have a detrimental impact on quality of life and might interfere with independent living. This Review discusses the tissue-selective side effects of endocrine therapies and specifically their impact on cognitive function, on the basis of clinical data; the neurobiological effects of endocrine therapies as observed in preclinical models are also discussed. We highlight the critical issues that need to be addressed in future preclinical and clinical studies in order to best assess the cognitive effects of endocrine treatment in patients with breast cancer.